Agency Cost Influence Toward Dividends Policy at Manufacturing Company Listed in IDX - Hermawati Liya; Harsono Edwin Puspita (Jurnal Akuntansi dan Keuangan (JAK), 2018)
Agency intereralation is a manager (agent) that is controlled by others with a contract of one or more shareholder. Manager has their own interest in decision making, but they also have a responsibality to maximize shareholder’s welfare. This conflict of interest always becomes a problem, that is agency problem. To solve this problem, will need some cost, namely agency cost that is related to dividens policy. The interelation between agency and shareholder is a new development to minimize agency cost. The research aims to prove the influence of agency cost towards dividends policy empirically. Dimention used to measure the agency cost is dispertion of ownership, managerial ownership, collateral assets, and debt policy, while dividens policy by dividen payout ratio. Sampling methode applied is purposive sampling, with financial report and company annual report as secondary data used. Sample used in this research is 27 manufacturing companies listed in Indonesia Stock Exchange (IDX) from 2010-2012. Analyzing method used is multiple regression through SPSS ver.16. the outcome of this research is dispertion of ownership, managerial ownership, collateral assets, and debt policy significantly influence in dividens policy partially.